Numerical analysis of the structural design of the Museum of Modern Art of Rio de Janeiro - MAM - Inojosa, Leonardo da Silveira Pirillo (2020)
In 1958 the definitive headquarters of the Museum of Modern Art of Rio de Janeiro - MAM was inaugurated, a project by Affonso Reidy between 1952 and 1953. MAM´s building is an architectural and historical landmark for Brazil, its importance is not limited to its function, like any important museum, its relevance goes beyond the limits of simple purpose and becomes an icon of an era, and of Rio de Janeiro. MAM is a symbol of both the evolution of museums in Brazil and the main representative of the “Carioca school” of modern architecture. The whole of the complex is formed by 3 blocks. The School Block, first to be opened in 1953; the Main Body, where is the exhibition gallery, object of study of this work, built in 1967; and finally the Theater, opened at the end of 2006. The area occupied by the Museum is 40 thousand square meters, surrounded by the sea and the gardens of Burle Marx at “Aterro do Flamengo”. Affonso Reidy was concerned, throughout the project process, not to influence the landscape of the place, leaving large open spaces on the ground floor and giving the building a lot of transparency. He also made natural use of the chosen materials, such as the concrete of the main block structure, which is structured by 12 reinforced concrete frames and 2 concrete gables at the ends, spaced every 10 m, overcoming spans of 26 m. Pillars that follow a striking architectural form, consistent with the needs of the efforts, form these porches. The objective of the present study is, by means of computational tools such as the SAP 2000 program, to understand the efforts to which the structure is subjected, verifying the constructive and aesthetic justifications of the structural solution and highlighting the importance of the structural system adopted for the architectural result.